Decision-making, affective states, and self–efficacy of students in the high–stress situation of a 192 m bungee jump – a randomised crossover trial - Wachholz, Felix; Wilhelm, Mavin; Frühauf, Anika; Niedermeier, Martin; Kopp, Martin (Cognition and emotion, 2025)
Decision-making involves rational and affective pathways, with high-stress potentially altering decision - making and affective states, alongside affecting behavioural variables. This study aims to analyze decision-making, affective states, and variables related to behaviour in a real-life high-stress scenario (bungee - jumping).Using a within-subject crossover-design, 19 participants (47% female, aged 23.0 ± 2.1 years) completed a 192 m bungee-jump and a 1 m control jump. Decision-making tests, affective states, and behavioural variables were assessed. Condition-by-time fully repeated measures analyses of variance were employed.Balloon Analogue Risk Task (BART) revealed significantly higher values pre - and post-bungee-jump compared to the control jump. Accuracy and average reaction time on the Go/No-Go task remained consistent across conditions and time points. Pre-action self-efficacy was significantly higher after the bungee - jump compared to the control jump. Affective valence demonstrated a significant condition-by-time interaction, presenting low values immediately before the bungee-jump.A high-stress situation impacted risk-taking but not inhibition in decision-making, associated with heightened arousal and affective valence. Anticipatory effects emerged significantly in decision-making and affective states. Furthermore, participants exhibited increased confidence in approaching subsequent tasks post - bungee - jump. Therefore, high-stress situations may enhance pre-action self-efficacy, although potential implications for riskier decision-making should be acknowledged.